Ultra-thin self-healing vitrimer coatings for durable hydrophobicity - Jingcheng Ma (Nature Portfolio, 2021)
By now a plethora of ultrathin hydrophobic coatings are available but their durability are not well developed. Here, the authors present a thin, durable and fluorine-free PDMS-based vitrimer coating that implements many desirable aspects like energy efficiency, durability and sustainability.